A Comparison of Surgical Outcomes of Hip Fractures with Mini-open Screw Fixation and with Closed Screw Fixation in Young Adults - Srisai, MD, Chinnawat; Sae-Jung, MD, PhD, Surachai (Journal of Southeast Asian Orthopaedics, 2022)
Background: Most femoral neck fractures in young adults (patients under 60) are caused by severe trauma and lead to complications such as nonunion and avascular necrosis. Two types of operations, mini-open reduction and screw fixation and closed reduction and screw fixation are commonly performed. However, the relative merits of these two techniques are still controversial. Objectives: To investigate the characteristics of young adult patients with femoral neck fractures and to compare surgical outcomes with mini-open reduction and screw fixation (mini open group) and patients undergoing closed reduction and screw fixation (CRSF group). Materials and Methods: The medical records of 77 young adult patients with hip fractures treated at Roi-Et Hospital in northeast Thailand from 2011 to 2016 were reviewed. The data, including patient characteristics and surgical outcomes, were statistically analyzed. Results: The mean age of the patients was 36.19±9.95 years. The main cause of hip fracture was motor vehicle accidents. Most of the injuries were basicervical fractures with no difference between males and females. There were no significant differences between patients in the mini open and the CRIF groups for screw placement, operative time, successful reduction of fracture, incidence of failure of fixation, achievement of bone union, and occurrence of avascular necrosis. The mini-open group, however, did have statistically significantly higher intraoperative blood loss and lower overall treatment costs than the mini open group. Conclusions: In clinical practice, mini-open reduction and internal fixation with cancellous non cannulated screws using the Watson-Jones approach and with a normal operating table is appropriate for treatment of young adults with hip fractures, especially when the cost of treatment is a major consideration.